Promoting participatory research in chronicity: The ESPRIMO biopsychosocial intervention for young adults with multiple sclerosis - Donisi, Valeria; Poli, Silvia; Mazzi, Maria Angela; Gobbin, Francesca; Schena, Federico; Del Piccolo, Lidia; Bigardi, Valeria; Gajofatto, Alberto; Rimondini, Michela (Frontiers in Psychology, 2022)
Background Co-creation allows to develop tailored interventions in chronicity and to increase patients’ engagement. Considering the interacting nature of physical, psychological, and social domains in multiple sclerosis (MS), a biopsychosocial approach to care is crucial. Aims This paper aims to present (i) an example of a co-creation process in the context of chronic diseases (ii) preferences and perspectives of young adults with multiple sclerosis (YawMS; aged 18–45) and healthcare professionals (HCPs) on the relevance, objectives, and modalities of a biopsychosocial intervention (named ESPRIMO) and on strategies/barriers to participation. Methods A participatory mixed-method approach in three consecutive steps was implemented: online surveys with YawMS (n = 121) and HCPs (n = 43), online focus groups (FGs) with YawMS, consultation with an advisory board (AB) composed by YawMS, HCPs and researchers. For the survey, descriptive statistics and inductive content analysis have been used for quantitative and qualitative analysis, respectively. FGs and AB were used to deepen the understanding of the survey’s results. Results An integrated intervention is extremely relevant according to the perspectives of the main stakeholders. Helping disease acceptance, providing stress management strategies, and supporting emotional expression emerged as the most relevant psychological objectives according to participants. Having tangible benefits, being tailored, and fostering interpersonal relationships emerged as the main preferred characteristics of physical activity. Preferences emerged on the modalities and timing of the intervention, with a venue unrelated to the disease strongly supported. Both HCPs and YawMS highlighted as the most valuable advantages of conducting the intervention online the increased accessibility, while the main limit was the restriction to social interaction (recognized as already limited during the COVID-19 pandemic). Accessibility and lack of time resulted as the main barriers to participation. Conclusion The co-creation process gave valuable information on preferences and perspectives of main stakeholders on objectives, modalities, and strategies to improve participation which has been used in the design of the ESPRIMO biopsychosocial intervention. Those results might inform future intervention development in the field of chronicity. The current paper outlined a co-creation methodology which might be replicated in future research on other conditions of vulnerability.